(untitled) (CIPEEX, 2025)
Introduction: Gas exchange is a central phenomenon for human physiology, involving the continuous release of oxygen and the removal of carbon dioxide. In the lungs, exchanges are carried out through the alveolar-capillary membrane, controlled by diffusion and partial pressures of gases. The understanding of gas exchange in cardiovascular and respiratory biophysics allows the understanding of the fundamentals of the processes that underline cellular metabolism and homeostasis. Objective: The present study aimed to analyze the mechanisms of O2 and CO2 diffusion in the lungs in the light of cardiovascular and respiratory biophysics, highlighting the physical factors that can influence the efficiency of gas exchange. Methodology: A narrative literature review was carried out between July and September 2025. Searches were conducted in the PubMed, Scielo and Google Scholar databases, using the descriptors "gas exchange", "diffusion", "cardiovascular biophysics" and "respiratory biophysics" and. Articles published in the last ten years in English and Portuguese that addressed theoretical and experimental studies on alveolar diffusion, as well as its relationship with cardiac function, were included. Results: The results show that the diffusion of these gases in the alveoli behaves according to Fick’s Law, which was shown to be influenced by variables such as surface area, membrane thickness and partial pressure gradients. The first variable leads part of the oxygen to diffuse from the alveoli to the pulmonary capillaries due to the higher partial alveolar pressure, with CO2 acting in the opposite direction, aided by its greater solubility and diffusion coefficient. Thus, cardiovascular biophysics maintains that cardiac output and the affinity of oxygen for hemoglobin are critical for the transport of gases correctly, according to what was found. When these parameters are altered, such as in the presence of respiratory and cardiac diseases, the efficiency of gas exchange is suboptimal, and hypoxia and hypercapnia may occur. Conclusion: Pulmonary gas exchange results from complex interactions between the respiratory and cardiovascular systems, governed by fundamental biological and physical laws. Understanding these mechanisms is essential for health professionals, as it guides clinical conduct and the development of therapeutic strategies in pathologies that affect respiratory and cardiovascular function.